Rsa encryption and decryption using matlab - Jam'aah, Suud (Universiti Malaysia Sarawak, (UNIMAS), 2004)
RSA encryption and decryption nowadays becomes the major part for secure transmissions of data in various types of networks. The aim of this project is to develop an application software and GUI (Graphical User Interface) using MATLAB that enable the user to select the RSA modulus bit length. There are three steps used such as key generation, encryption and decryption. Two large primes generated to find the public key and private key. The choice of bit length in this project is 512, 768, 1024 and 2048 bits. The bit length selection depends on the application as explained in this report. The performance of this program depends on running time of the program and the strength of this program depends on the difficulty to find the private key.